Analisis Alih Kode dan Campur Kode Novel Private Bodyguard - Riska, Masya; Kurnia, Ita; Kusuma, Emelda; Nur, Riska (Institut Nalanda, 2024)
Literary works are the result of the author’s feelings expressed through beautiful presentations or reflections of oursevels. He was born to explain or describe the human form. This research aims to analyze code switching and code mixing in the novel Private Bodiguard by Caroline Puspojudo. This research uses a qualitative descriptive method carried out by means of document study. This type of research also uses parts or quotations from the novel Private Bodyguard. In this research, the technique of reading and then noting is used, which is included in code switching and code mixing in the novel Private Bodyguard by Caroline Puspojudo. In this novel, code switching and code mixing together total 101. However, in this novel, code mixing is more dominant than code switching.